TRANSDUCERS 2009 - 2009 International Solid-State Sensors, Actuators and Microsystems Conference 2009
DOI: 10.1109/sensor.2009.5285519
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of AuSi eutectic wafer bonding

Abstract: In this paper, wafer-to-wafer AuSi eutectic bonding was investigated and evaluated with various sets of experimental parameters. Single crystalline Si and amorphous Si were bonded with different dimension Au layers and observed by optical measurements. Material composition, adhesion layer, electrical insulation, bonding parameters, and surface pre-treatments were discussed and have improved bonding performance. Bond strength determined by micro-chevron-test and shear test was evaluated as well as hermeticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…In most cases Si is coming from the substrate, what means, that it seems to be available unlimited. So the solidification starts with the mismatch of eutectic mixture at a certain process temperature [11].…”
Section: Theoretical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases Si is coming from the substrate, what means, that it seems to be available unlimited. So the solidification starts with the mismatch of eutectic mixture at a certain process temperature [11].…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…The bonding temperature, tool pressure and duration are seen to be the most important parameter for reaching a high bonding quality. The most influence on flow behavior is given by temperature and pressure [11]. Thus, the temperature ranged from 390 °C to 400 °C while a tool pressure of 100 kPa to 500 kPa was applied between 5 minutes and over a period of 20 minutes respectively for the AuSi wafers.…”
Section: Bonding Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to improve the Au/Si bonding performance. It was reported by Chen et al [6], Lin et al [7] and Jing et al [8] that an improved contact interface can be obtained by conducting the Au/a-Si (amorphous Si) reaction. Previous works about the Au/a-Si bonding were all based on the PECVD method to form the amorphous Si on top of the Si wafer before bonding.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that an a-Si layer on a (1 0 0) Si wafer rapidly reacts with the Au layer and forms a uniform Au(Si) liquid alloy, which prevents the formation of air voids at the bond interface. Lin et al studied the development of and evaluated Au Si eutectic wafer bonding [16]. In their work, material composition, adhesion layer, electrical insulation, bonding parameters and surface pre-treatments were discussed in terms of bond performance.…”
Section: Introductionmentioning
confidence: 99%